Neonovi prikazki . Neon Light Tales - Traikova, Eldora (Vreme Studio for Documentary Films and Bulgarian National Television, 1992)
The touching story of the homeless people: young gypsy prostitutes, jobless people without a shelter, and old hobos, living at the Central Railway Station in Sofia. Some are happy when they have a crust of bread or a penny tossed by a stranger, others are enraged by the humiliation they endure each and every day. The film is shot in black and white and the piercing neon light of the public building at night renders the dire circumstances of its inhabitants.